ALG6‐CDG: a recognizable phenotype with epilepsy, proximal muscle weakness, ataxia and behavioral and limb anomalies. Issue 5 (10th June 2016) - Morava, Eva; Tiemes, Vera; Thiel, Christian; Seta, Nathalie; de Lonlay, Pascale; de Klerk, Hans; Mulder, Margot; Rubio‐Gozalbo, Estela; Visser, Gepke; van Hasselt, Peter; Horovitz, Dafne D. G.; de Souza, Carolina Fischinger Moura; et al.
Abstract: Introduction: Alpha‐1, 3‐glucosyltransferase congenital disorder of glycosylation (ALG6‐CDG) is a congenital disorder of glycosylation. The original patients were described with hypotonia, developmental disability, epilepsy, and increased bleeding tendency. Methods: Based on Euroglycan database registration, we approached referring clinicians and collected comprehensive data on 41 patients. Results: We found hypotonia and developmental delay in all ALG6‐CDG patients and epilepsy, ataxia, proximal muscle weakness, and, in the majority of cases, failure to thrive. Nine patients developed intractable seizures. Coagulation anomalies were present in <50 % of cases, without spontaneous bleedings. Facial dysmorphism was rare, but seven patients showed missing phalanges and brachydactyly. Cyclic behavioral change, with autistic features and depressive episodes, was one of the most significant complaints. Eleven children died before the age of 4 years due to protein losing enteropathy (PLE), sepsis, or seizures. The oldest patient was a 40 year‐old Dutch woman. The most common pathogenic protein alterations were p.A333V and p.I299Del, without any clear genotype–phenotype correlation. Discussion: ALG6‐CDG has been now described in 89 patients, making it the second most common type of CDG. It has a recognizable phenotype and a primary neurologic presentation.